2020
DOI: 10.1186/s12957-020-1798-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-192 promotes the development of nasopharyngeal carcinoma through targeting RB1 and activating PI3K/AKT pathway

Abstract: Background: The dysregulation of microRNAs (miRNAs) has been found in diseases and cancers, including microRNA-192 (miR-192). This study was designed to investigate the role of miR-192 in nasopharyngeal carcinoma (NPC) progression. Methods: The expression levels of miR-192 and some genes were assessed by qRT-PCR and Western blot. The function of miR-192 was investigated through MTT, Transwell, and dual-luciferase reporter assays. Results: The expression of miR-192 was increased in NPC tissues, and high miR-192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…3F). Among these, the PI3K-Akt pathway has been previously implicated in NPC progression [24,25]. Our ndings are in line with those of previous studies.…”
Section: Go and Kegg Of Predicted Target Genessupporting
confidence: 93%
See 1 more Smart Citation
“…3F). Among these, the PI3K-Akt pathway has been previously implicated in NPC progression [24,25]. Our ndings are in line with those of previous studies.…”
Section: Go and Kegg Of Predicted Target Genessupporting
confidence: 93%
“…Early diagnosis of NPC is a key strategy for improving the prognosis of patients [25,26]. However, accurate early diagnosis of NPC is typically challenging [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tissue-derived and serum-exosomal expression of miR-192-5p could discriminate between PDAC and HCs with good accuracy, similar to that of established tumor marker CA.19-9. However, the clinical value of miR-192-5p remains ambiguous, as previous studies investigating its regulation in PDAC revealed in part contradictory results ( Table S1 [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]). For the first time in 2013, Zhao et al described an overexpression of miR-192-5p in tumor tissue and blood serum of PDAC patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decreased levels of circulating miR-192-5p were shown to correlate with presence of bone metastasis in non-small cell lung cancer (NSCLC) [ 37 ]. Contrarily, its upregulation in tissue of esophageal squamous cell carcinoma, prostate cancer, and nasopharyngeal carcinoma illustrated the different tumor specific signatures of miR regulation [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, radiotherapy and chemotherapy remain the standard treatments for late-stage NPC. 1 , 2 Despite the improvement of radiotherapy and chemotherapy in combating NPC, recurrence and metastasis are frequently observed in patients. 3 Hence, promising biomarkers and curative options are urgently warranted to improve the clinical prognosis in patients with NPC.…”
Section: Introductionmentioning
confidence: 99%